PENGARUH KECERDASAN EMOSIONAL KARAKTERISTIK INDIVIDU DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PADA PT. PRIMA INTI NUSA MEDAN - Munthe, Andika Supriadi; Tarigan, Miska Irani; Sitanggang, Darna; Sinaga, Ria Veronica (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
This study seeks to ascertain the impact of emotional intelligence, personality traits, and work loyalty on employee performance at PT. Prima Inti Nusa Medan. Data was collected using surveys, documentation, and interviews. The research approach employed was quantitative, with 33 respondents selected using purposive sampling. The data in this study was analyzed using SPSS version 26.00. The findings indicate that emotional intelligence, individual qualities, and work loyalty have a partly favorable effect on employee performance.The coefficient of determination is 0.839, indicating that 83.9% of employee performance can be explained by the variables of emotional intelligence, individual traits, and job loyalty, with the remaining 16.1% explained by factors not addressed in this study.